Comparative efficacy and tolerance of centrally acting muscle relaxants in elderly patients with nonspecific musculoskeletal pain - R. V. Gorenkov (Nevrologiâ, Nejropsihiatriâ, Psihosomatika, 2020)
Objective: to evaluate the clinical efficacy and tolerability of the Russian drug tolperisone (calmyrex) versus tizanidine and baclofen in the therapy of acute nonspecific musculoskeletal pain (NSMSP) in the elderly.Patients and methods. Examinations were made in 135 elderly (60–75-year-old) patients with acute NSMSP. To relieve pain syndrome, all the patients were prescribed nimesulide suspension 100 mg twice a day after meals. The patients were randomized using an envelope method to three groups, each of which took a muscle relaxant as tablets for 15 days: Group 1 received the Russian drug tolperisone (calmyrex) 150 mg thrice a day; Group 2 used tizanidine 2 mg thrice a day; Group 3 had baclofen 10 mg twice a day. Pain syndrome was rated on a visual analogue scale (VAS). To measure orthostatic blood pressure, to check the coordinator system, and to record adverse events (AEs) were mandatory.Results and discussion. At 15 days, treatment substantially reversed pain syndrome according to VAS scores in all the groups: from 68 to 14 in Group 1, from 64 to 17 in Group 2, and from 62 to 18 in Group 3 (without significant differences between the groups). AEs were more common in Groups 2 and 3 patients who received tizanidine or baclofen. Orthostatic hypotension was reported in 3 patients taking baclofen. The high safety and good tolerability of a combination of a non-steroidal anti-inflammatory drug (NSAID) and a muscle relaxant were noted in the calmyrex group.Although muscle relaxants ensure clinically significant short-term pain relief in acute nonspecific back pain, it is necessary to take into account that elderly patient can develop AEs when taking the drugs, which is associated with delayed metabolic reactions, reduced hepatic blood flow and glomerular filtration rate, and a larger number of diseases and used medications.Conclusion. Therapy with NSAIDs and centrally acting muscle relaxants for acute NSMSP in elderly people calls for special precautions due to the fact that there may be AEs that are less likely to occur with calmyrex than with tizanidine and baclofen.